Salaam Aleykum Copenhagen - Niskač, Sašo (3 Little Wolves Production, 2007)
Verzio FF Submission Salaam Aleykum Copenhagen is a short documentary about Haluk, Iman and Allan – three young people with Turkish, Kurdish, Lebanese and Danish backgrounds living in Copenhagen. They talk about immigration and integration, their daily problems and challenges, family values, their view on Danish society and Copenhagen itself. While presenting their worlds they are opening the doors towards understanding a new kind of Copenhagen.